Radošās darbības veicināšana mājturības un tehnoloģiju stundās 1.-4.klasē - Katkovska, Aija (Latvijas Universitāte, 2012)
Diplomdarba tēma: „Radošās darbības veicināšana mājturības un tehnoloģiju stundās 1.- 4. klasēs.” Diplomdarba apjoms: 4 nodaļas, 74 lpp., 1 attēls, 16 tabulas, 14 pielikumi, izmantoti 35 literatūras avoti. Diplomdarba mērķis: Izstrādāt, pamatot un praksē pārbaudīt radošās darbības veicināšanas iespējas mājturības un tehnoloģiju stundās 1.- 4. klasēs. Darbā analizēta radošā darbība, psihiskās izziņas procesi un raksturotas iztēles veidu īpatnības 1.- 4. klasēs. Veikta pedagoģiskā izmēģinājuma darbība ar mērķi veicināt skolēnu radošo darbību. Izstrādāts mācību satura apguves plānojums un piedāvātas praktiskas nodarbības un uzdevumi skolēnu radošās darbības veicināšanai. Atslēgas vārdi: radošā darbība, iztēle, emocijas, psihiskās izziņas procesi.

Diploma paper subject: Promoting the creative activity in lessons of home economics and technologies in Grades 1 - 4. Although many scholars have discussed and investigated the advantages of promoting the creative activities in the lessons of home economics and technologies in the elementary school and in particular its motivating aspect little research has been undertaken. The purpose of the diploma paper is to folder a deeper understanding of this teaching method, and how it can be used to raise creativity and motivation in a real classroom setting. The results obtained suggest that promotion of the creative activities in lessons of home economics and technologies enchances students intrinsic and extrinsic motivation and therefore using different creative tasks should be as a complement to every bigger theme with the aim to promote students creativity.
Promoting the creative activity in lessons of home economics and technologies in Grades 1 -4
Keywords: Pedagoģija